2012
DOI: 10.1016/j.jdent.2012.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Long-term protective effect of surface sealants against erosive wear by intrinsic and extrinsic acids

Abstract: OBJECTIVE: To test sealants to prevent erosive tooth wear caused by extrinsic and intrinsic acids under long-term exposition. METHODS: 144 bovine enamel samples were randomly allocated to twelve groups (1-12). Samples of groups 1, 5 and 9 remained unsealed (positive controls), 2, 6 and 10 were sealed with Silicon Seal Nano Mix and 3, 7 and 11 with SealProtect. Groups 4, 8 and 12 were sealed with flowable composite (negative controls). Groups 1-4 were immersed in artificial saliva, 5-8 in hydrochloric acid and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 40 publications
2
28
0
9
Order By: Relevance
“…The results of studies [36,37] using pepsin admixture to hydrochloric acid for erosion simulation are inconclusive. Therefore, in the present study, the erosive attack was performed with pure hydrochloric acid, as performed in numerous other studies [12,14,19,24,38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of studies [36,37] using pepsin admixture to hydrochloric acid for erosion simulation are inconclusive. Therefore, in the present study, the erosive attack was performed with pure hydrochloric acid, as performed in numerous other studies [12,14,19,24,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Later, coating of teeth with a resin-based surface sealant showed a significant protective effect against erosive/abrasive tooth wear under in-vivo and in-vitro conditions [22,23]. A recent in-vitro study found a significant reduction of erosive demineralisation by using surface sealants as a coating, even when samples were stored for 4 days in hydrochloric acid or 24 days in citric acid [24]. However, in that study only a demineralisation without an additional abrasive wear regime or remineralisation periods was performed.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to state that in other investigations, the resin sealant, when used as a coating, was capable of significantly reducing the enamel demineralization caused by acids and its protective effect seemed to last longer than the protective effect of rinsing solutions [11]. This fact reveals a limitation of the present investigation, since it was impossible to determine if the increase in roughness in the groups covered with resin sealant was the result of alterations in the surface of the material itself or if it was totally or partially removed, exposing the surface of the composite resin to the acids.…”
Section: Discussionmentioning
confidence: 99%
“…Resin materials are affected by chemical substances in the oral cavity, which interfere with its organic matrix, causing a softening of polymers and consequently, affecting surface properties, such as roughness [8][9][10]. Despite many studies showing the importance of the use of fluorides and mechanical barriers on dental surfaces exposed to erosion [2,5,7,[11][12][13], further analysis is required to study their effects on restorative materials subjected to the same process.…”
Section: Introductionmentioning
confidence: 99%
“…The specimens were then subjected to initial erosion with 0.3% citric acid solution (pH = 2.6) for 5 minutes, to produce a softened layer over the enamel surface, normally found on eroded teeth which need treatment. 23 For that, the samples were identified, placed in silicone holders, and immersed inside the acid solution, over a Kline multifunctional shaker at an average speed of 120 rpm, avoiding the saturation of calcium acid in contact with the sample, which would reduce their activity. The proportion used was 10 mL of citric…”
Section: Preparation Of the Specimensmentioning
confidence: 99%